Christian Metz and the Codes of Cinema Film Semiology and Beyond - Tröhler, Margrit; Kirsten, Guido; Zutavern, Julia (Film Theory in Media History, 2018)
A pioneering figure in film studies, Christian Metz proposed countless new concepts for reflecting on cinema, rooted in his phenomenological structuralism. He also played a key role in establishing film studies as a scholarly discipline, making major contributions to its institutionalisation in universities worldwide. This book brings together a stellar roster of contributors to present a close analysis of Metz's writings, their theoretical and epistemological positions, and their ongoing influence today.